Qualitative methods and evaluation research. The case of evaluation of a postgraduate program - Χριστοδούλου, Μιχάλης; Κουϊμτζή, Ελένη Μαρία (Education Sciences, 2024)
The aim of the present article is to highlight the contribution of qualitative methods to evaluation research. For this purpose, we present the research design and the findings from evaluation research that we carried out in a postgraduate program (MSc) of a Greek university. Emphasis is placed on methodological details, such as the relevance between interview guide and data analysis, the process of analysis through Template Analysis (TA) and the way of presenting the data. TA was chosen because codes are depicted as in the form of hierarchical dendrograms. The use of TA has an additional methodological benefit since dendrograms can provide the base for constructing a quantitative research instrument in a succeeding study. In that sense we embrace the idea that qualitative methods can fruitfully be brought into dialogue with quantitative methods when designing evaluation research.